Analisis Penerimaan Informasi Kesehatan Pada Aplikasi Telemedicine Menggunakan Model TAM & IAM - Diddo Adding Adove; Ucha Indra Gunawan; Yuli Maylena; Ruswati Ruswati; Grara Vema Tuzauna; Mimin Sumiyati; Firda Mokodongan (Jurnal Ners, 2026)
This study aims to examine the effects of information quality, information credibility, and information ease of use on information usefulness, as well as the effects of information usefulness and information adoption on the intention to continue using telemedicine applications. A quantitative research approach was employed using a survey method involving 426 telemedicine application users in Indonesia, selected through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3 software. The findings reveal that information quality, information credibility, and information ease of use have positive and significant effects on information usefulness. Furthermore, information ease of use and information usefulness positively and significantly influence information adoption. In addition, both information usefulness and information adoption are found to have positive and significant effects on the intention to continue using telemedicine applications. These findings suggest that telemedicine service providers should enhance the quality, credibility, and accessibility of health information to improve users' perceptions of information usefulness, encourage information adoption, and strengthen the continued use of telemedicine applications. This study contributes to the development of the Information Adoption Model (IAM) and the Technology Acceptance Model (TAM) in explaining users' continuance intention toward digital healthcare services.